The attribution of creativity and agency to artificial intelligence - Siah, Dorothy Tian Xin (Nanyang Technological University, 2024)
Given the entrance of AI into spaces that have traditionally been creative, the philosophical discourse about creativity has been renewed with more debates that question our intuitions surrounding creativity. Taking on Boden’s functionalist theory of creativity, I examine how we might attribute creativity to existing AI systems. In my evaluation of Boden’s theory, I suggest an addition of the agency requirement in the judgement of creativity to provide a bridge between Boden’s output-centred theory and her critics’ process-centred theory of creativity.